Electrochemical Studies of Copper(II) Complexes with Oxoglutarate at Dropping Mercury Electrode in Aqueous Medium - Gupta, O.D.; Singh, Jyoti (Asian Journal of Chemistry, 2010)
The composition and stability constants of complexes formed by copper(II) with oxoglutarate have been investigated in aqueous medium. The complexes with metal to ligand ratio as 1:1, 1:2, 1:3 have been reported at pH 6.8. The values of formation constants log β1 = 2.66, log β2 = 3.34, log β3 = 4.37 at 303 K and log β1 = 2.14, log β2 = 3.32, log β3 = 3.39 at 313 K were calculated by DeFord and Hume method. The mathematical Mihailov method was also used. Thermodynamic functions and kinetic parameters have been determined.